Influenza Infection Induces Neuroinflammation, Alters Hippocampal Neuron Morphology, and Impairs Cognition in Adult Mice - Jurgens, Heidi A. (Society for Neuroscience, 2012)
Influenza is a common and highly contagious viral pathogen, yet its effects on the structure and function of the CNS remain largely unknown. Although there is evidence that influenza strains that infect the brain can lead to altered cognitive and emotional behaviors, it is unknown whether a viral strain that is not neurotropic (A/PR/8/34) can result in a central inflammatory response, neuronal damage, and neurobehavioral effects. We hypothesized that neuroinflammation and alterations in hippocampal neuron morphology may parallel cognitive dysfunction following peripheral infection with live influenza virus. Here, we show that influenza-infected mice exhibited cognitive deficits in a reversal learning version of the Morris water maze. At the same time point in which cognitive impairment was evident, proinflammatory cytokines (IL-1β, IL-6, TNF-α, IFN-α) and microglial reactivity were increased, while neurotrophic (BDNF, NGF) and immunomodulatory (CD200, CX3CL1) factors were decreased in the hippocampus of infected mice. In addition, influenza induced architectural changes to hippocampal neurons in the CA1 and dentate gyrus, with the most profound effects on dentate granule cells in the innermost portion of the granule cell layer. Overall, these data provide the first evidence that neuroinflammation and changes in hippocampal structural plasticity may underlie cognitive dysfunction associated with influenza infection. In addition, the heightened inflammatory state concurrent with reduced neurotrophic support could leave the brain vulnerable to subsequent insult following influenza infection. A better understanding of how influenza impacts the brain and behavior may provide insight for preventing inflammation and neuronal damage during peripheral viral infection.